To solve the given problem, first, we need to identify the two correct equations from the provided options and then graph the system of equations.
Part A: Selecting the Equations
-
We know the sum of the ages of the two brothers: \[ x + y = 6 \] (where \(x\) is the age of the younger brother and \(y\) is the age of the older brother.)
-
The age of the older brother is two more than triple the square of the age of the younger brother: \[ y = 2 + 3x^2 \]
So the correct equations that represent this situation are:
- Equation 1: \(x + y = 6\)
- Equation 2: \(y = 2 + 3x^2\)
Part B: Solving the System by Graphing
Now, let's graph these two equations and find the intersection, which would give us the solution.
-
Graph of \(x + y = 6\):
- To find the y-intercept, set \(x = 0\): \[ y = 6 \]
- To find the x-intercept, set \(y = 0\): \[ x = 6 \]
- Points: (0, 6) and (6, 0). Draw a straight line between these two points.
-
Graph of \(y = 2 + 3x^2\):
- This is a parabola opening upwards.
- Find y-values for different x-values:
- When \(x = 0\): \[ y = 2 + 3(0)^2 = 2 \quad \text{(Point: (0, 2))} \]
- When \(x = 1\): \[ y = 2 + 3(1)^2 = 5 \quad \text{(Point: (1, 5))} \]
- When \(x = -1\): \[ y = 2 + 3(-1)^2 = 5 \quad \text{(Point: (-1, 5))} \]
- When \(x = 2\): \[ y = 2 + 3(2)^2 = 14 \quad \text{(Point: (2, 14))} \]
- Sketch the parabola through the points calculated.
Finding the Intersection:
To find where these two graphs intersect, we can solve for \(x\) and \(y\) using either algebraically or graphically by locating the point of intersection.
Algebraic Method:
Substituting \(y\) from the first equation into the second: \[ 6 - x = 2 + 3x^2 \]
Rearranging gives: \[ 3x^2 + x - 4 = 0 \]
Now solving the quadratic: Using the quadratic formula, \(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\):
Where \(a = 3\), \(b = 1\), and \(c = -4\):
\[ x = \frac{-1 \pm \sqrt{1^2 - 4 \cdot 3 \cdot (-4)}}{2 \cdot 3} \] \[ x = \frac{-1 \pm \sqrt{1 + 48}}{6} \] \[ x = \frac{-1 \pm \sqrt{49}}{6} \] \[ x = \frac{-1 \pm 7}{6} \]
Calculating the two possible solutions for \(x\):
- \( x = 1 \)
- \( x = -\frac{4}{3} \) (not valid since age cannot be negative)
Therefore:
\(x = 1 \) gives us the younger brother's age. Calculating \(y\): \[ y = 6 - x = 6 - 1 = 5 \]
Solution:
In words: The younger brother is 1 year old and the older brother is 5 years old.
Graph:
To visualize the solution graphically, you would plot both equations on a graph with \(x\) on the horizontal axis and \(y\) on the vertical axis, indicating the intersection point \((1, 5)\).
If you need a graphical representation, you can use graphing software or tools like Desmos to create the graph based on the equations provided.